A proposal of a hydrodynamic model to low Reynolds numbers in a liquid-solid inverse fluidized bed reactor - Campos Díaz, Karla Edith; Alvarez Cruz, José Luis (Tecnología y ciencias del agua, 2017)
Campos-Díaz, K. E., & Alvarez-Cruz, J. L. (May-June, 2017). A proposal of a hydrodynamic model to low Reynolds numbers in a liquid-solid inverse fluidized bed reactor. Water Technology and Sciences (in Spanish), 8(3), 143-150.This paper examines the fundamental characteristics of an inverse liquid- solid inverse fluidized bed reactor. In this reactor, many experiments were performed using three sizes of polypropylene spherical solids, lighter than water, with different diameters (4.00, 4.16 and 4.18 mm) and of densities ranging from 808 to 867 kg/m3 , these were fluidized by continuous liquid phase flow. Various bed heights were obtained at different flowrates from 0.95 to 9.5 (L min-1). A predictive model is developed for the hydrodynamic behavior, such as height and solid holdups (bed porosity), this model was derived from the balance of forces acting on a single particle and the set of particles found in the fluidized bed; uses process parameters, such as reactor dimensions, particle properties, and liquid flowrates as input variables, this model also includes the inertial drag coefficient which allow extended a non-spherical particles. This model has several advantages when compared with previously reported. Among them, advantages such as standard deviation values â‰¤0.9% between experimental and calculated bed porosity, the bed porosity can be expressed in terms of the Reynolds and Archimedes numbers and this model estimate bed porosity in a range of Reynolds number from 5.5 to 200 which has not been studied in an inverse fluidized bed reactors.